2017
DOI: 10.4236/health.2017.911107
|View full text |Cite
|
Sign up to set email alerts
|

CCL4 Levels Differ between Aspirin-Tolerant and Aspirin-Intolerant Patients with Asthma

Abstract: Aspirin-exacerbated respiratory disease (AERD) is an asthma phenotype characterized by nasal polyps, chronic hypertrophic eosinophilic sinusitis, asthma, and sensitivity to aspirin. Unawareness of this disease by patients and their physicians may have serious consequences because of the risk of near-fatal asthma. Its confirmative diagnosis can be established only by provocative aspirin challenge, which represents a potential risk for patient health. Purpose: Because CCL4 plays an important role in several pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…One recent study showed that MIP-1β level was higher in N-ERD patients than in NSAIDs tolerant asthmatics in serum and nasal lavage; however, they included N-ERD subjects with significantly higher FEV1% than N-TA, which suggests that they were not matched according the disease severity. 10 It is noteworthy that we also observed higher levels of MIP-1β in the nasal samples in N-ERD than in N-TA subjects at both visits, although these differences were not statistically significant. In conclusion, it seems that MIP-1β may be an interesting marker of eosinophilic asthma depending on the severity of the disease and its phenotype; however, this observations should be further explored.…”
Section: Clinical Trials Showing the Effectiveness Of Mepolizumab Incontrasting
confidence: 52%
See 1 more Smart Citation
“…One recent study showed that MIP-1β level was higher in N-ERD patients than in NSAIDs tolerant asthmatics in serum and nasal lavage; however, they included N-ERD subjects with significantly higher FEV1% than N-TA, which suggests that they were not matched according the disease severity. 10 It is noteworthy that we also observed higher levels of MIP-1β in the nasal samples in N-ERD than in N-TA subjects at both visits, although these differences were not statistically significant. In conclusion, it seems that MIP-1β may be an interesting marker of eosinophilic asthma depending on the severity of the disease and its phenotype; however, this observations should be further explored.…”
Section: Clinical Trials Showing the Effectiveness Of Mepolizumab Incontrasting
confidence: 52%
“…In the study of Suzukawa M et al, 6 clinical response to mepolizumab was correlated with the serum MIP‐1 β, and patients with lower baseline levels of this chemokine had a worse response to the treatment. One recent study showed that MIP‐1β level was higher in N‐ERD patients than in NSAIDs tolerant asthmatics in serum and nasal lavage; however, they included N‐ERD subjects with significantly higher FEV1% than N‐TA, which suggests that they were not matched according the disease severity 10 . It is noteworthy that we also observed higher levels of MIP‐1β in the nasal samples in N‐ERD than in N‐TA subjects at both visits, although these differences were not statistically significant.…”
Section: V0 V4 V24 Friedman Anova Post Hoc Test P V0 Vs V4 P V0 Vs V2...mentioning
confidence: 98%